Recent Study on the Impact of Compensation and Benefits on Job Satisfaction - Calvin Mzwenhlanhla Mabaso; Bongani Innocent Dlamini (Insights into Economics and Management Vol. 7, 2021)
Background and Objective: Human capital is the pivotal of organisational effectiveness and the most valuable asset available to an organisation is its people. Retaining employees in their jobs is crucial for any organisational productivity and competitiveness. The shortage of academic staff and inability for higher Education Institutions to attract and retain highly qualified talent is a critical phenomenon in tertiary education. Academic staff are the employees of the educational organizations and their job satisfaction promotes teaching and learning. Satisfaction of academic staff will increase productivity and increase research outputs for the universities. The aim of the study was to investigate the impact of compensation, benefits on job satisfaction among academic staff in higher education institutions in a South African context. There is paucity on research investigating specifically the relationship between compensation, benefits and job satisfaction within the higher education institutions nationally. Materials and Methods: This study employed the quantitative research method to investigate the influence of rewards on talent attraction and retention. An explanatory hypothesis generating approach was employed and a survey design was used to collect data through a semi-structured questionnaire. A sample of 279 academic staff, which was the total population of participants were selected for this study. Results: A positive and significant effect of compensation on job satisfaction (p = 0.263). Moreover, there were no significant effect between benefits and job satisfaction. Therefore, only compensation significantly predicted job satisfaction among academic staff. Conclusion: The practical managerial implications that are attracting and retaining the new generation of lecturers into higher education institutions will require substantially different skills and attractive employment offers than what the higher education institutions presently offer. Therefore, higher education institutions must improve their compensation strategy in order to boost employees’ dedication that will enable commitment, while efficiently deliver outstanding results. This will improve research outputs and improve skills within the country. An electronic method of data collection should be considered to reduce time and cost of travelling to different campuses, which would enable academic staff to complete online surveys.